The Influence of Seal Kit Performance on the Pressure of Hydraulic Press Part Roll Cylinder in the Paper Industry - Kurniawan, Muhammad Helmi; Khusnul Khotimah Ayuningtiyas (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2023)
The hydraulic system is an energy transmission system utilizing liquid fluids. Liquids possess a characteristic different from solids in their inability to withstand shear stress. The employed methodology is qualitative research, also referred to as naturalistic qualitative research, which entails a natural implementation without manipulating circumstances. This study aims to identify the causes of damage to the hydraulic system in the press section machine, along with implementing appropriate corrective measures, while examining the hydraulic functioning of the press section machine. The research problem specifically focuses on analyzing the damage to the hydraulic cylinder and addressing cylinder seal failure. The damage results from seal wrinkling caused by aging, heat and wear. It is important to ensure that the hydrostatic test pressure is carried out at pressures up to 20 MPa with a holding time of at least 30 seconds. This examination ensures that the hydraulic roll press problem has been fully resolved and will not reoccur. Hydraulic systems offer numerous advantages as an energy source in various applications. These advantages include their lightweight nature, ease of installation, and low maintenance requirements. Inadequate performance in the hydraulic roller pressure section is attributed to a hydraulic cylinder seal that does not meet the specified standards, necessitating replacement with a suitable seal.